Analisis Faktor Risiko Terjadinya Keluhan Muskuloskletal pada Pengajar SMP dan MTs di Kabupaten Musi Rawas Tahun 2025 - Fitria Lindayani; Yuli Hartati; Sri Utari; Nugi Nurdin (Universitas Muhammadiyah Manado, 2026)
Complaints related to the musculoskeletal system are a common health threat faced by workers. The causes of MSDs include internal/individual factors (age, gender, BMI, length of service, lifestyle), occupational factors (length of service, work position, workload, frequency), and environmental factors (vibration, temperature). This study aims to analyze the relationship between individual factors (age, gender, body mass index, and physical activity) and occupational factors (length of service and work posture) on musculoskeletal disorders in junior high school (SMP) and Islamic junior high school (MTS) teachers in Musi Rawas Regency. This study used a quantitative cross-sectional approach. The study was conducted from February to April 2025. The population in this study were all 142 junior high school teachers in Muara Kelingi District, Musi Rawas Regency, with a sample size of 65 taken using simple random sampling. The research instrument used a questionnaire. Univariate analysis results indicate that the percentage of each dependent and independent variable is good. The Chi-square statistical test results in the bivariate analysis indicate a relationship between individual factors (age, gender, body mass index, and physical activity) and occupational factors (length of service and work posture) and musculoskeletal disorders in junior high school teachers in Musi Rawas Regency, with a p-value <0.05. Multivariate analysis results indicate that the most dominant factor contributing to musculoskeletal disorders in junior high school and Islamic junior high school teachers in Musi Rawas Regency is work posture.